Pengembangan Gim Edukasi Matematika Dasar berbasis Android - Sendi Rachmat Fadillah; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
These days technology is growing rapidly throughout the world. One of the technologies that is growing rapidly is mobile information and communication technology (smartphones). Many elementary school students in Indonesia now use smartphones just to play games. As a result, enthusiasm for learning, especially in mathematics began to decrease. Mathematics is still a subject that is considered difficult, especially by elementary school level students. This research will develop an educational game with android-based with mathematical theme. The goal is to help elementary school level students to increase their enthusiasm for learning in mathematics through learning media in the form of games. In its development the researcher using the Game Development Life Cycle method. There are 6 stages including Initiation, Pre-Production, Production, Testing, Beta, and Release. The test will be carried out using the Test Flow Diagram method to test the gameplay flow based on the player's point of view. For Beta testing in this study using the Fun Testing method. Players will try the games that have been made then fill out the questionnaire. The results of the Test Flow Diagram test show that the gameplay flow is going well. Whereas the results of Fun Testing on the level of pleasure of players in playing this educational game are 85% of 20 elementary school level students in grades 1 to 3.